Toward a Strategic Approach to Enhance Brand Equity Among Private Healthcare Providers in Indonesia - Sumendap, Bruce Gerald Jones (Green Publisher Indonesia, 2025)
Value creation is a core function in the marketing management process, and marketing to brand equity relationship can be found in literature. Yet, the effects of value creation on brand equity have not been sufficiently addressed. Scholars suggest that another critical dimension is added as a predictor of brand equity, which is ambidextrous leadership, as it supports the realization of marketing strategy implementation and value creation. The purpose of this study is to investigate the relationship between value creation, marketing strategy, and ambidextrous leadership, and how these factors affect brand equity. The literature review focused on theories, definitions, concepts, and dimensions of the variables under study. A quantitative methodology is chosen wherein the quantitative data will be collected and analyzed using statistical tools and interpreted to test the 4 hypotheses. The measurement and conceptual model to depict the hypothesized relationship will be evaluated based on 150 hospital managers in Indonesia, using a cross-sectional survey design. By empirical analysis, the study showed the significant effects of value creation (VC) and marketing strategy (MS) on brand equity as moderated by ambidextrous leadership (AL). A proposed model becomes a valuable contribution to the subject of brand equity. The findings from the study show that value creation is a well-integrated and strategic component of healthcare providers. Healthcare provider managers demonstrate a significantly high adoption of marketing strategies. Further, healthcare provider managers view their institutions as having stronger brand equity in terms of quality perception and awareness. Overall, the healthcare providers’ brand equity has a significant collective effect on their value creation efforts.